2000
DOI: 10.1046/j.1365-313x.2000.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that endo‐1,4‐β‐glucanases act on cellulose in suspension‐cultured poplar cells

Abstract: SummarySuspension-cultured poplar (Populus alba) cells produce two distinct endo-1,4-b-glucanases, one of which is released in the extracellular culture medium and the other localized in their walls. Two cDNA clones, PopCel1 and PopCel2, isolated from a poplar cDNA library, encode the extracellular and the wallbound endo-1,4-b-glucanases, respectively, based upon deduced amino acid sequences. The products of these two genes contained domains conserved in endo-1,4-b-glucanase (family 9) and showed 91.5% amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 47 publications
(56 reference statements)
3
48
0
2
Order By: Relevance
“…Upregulation of AtCel2 triggered by high sucrose concentration in the medium indicates its involvement in cellulose biosynthesis as previously suggested by Ohmiya et al (2000) and Shani et al (2006) for other endo-1,4-b-glucanases. Putative cell wall substrates of secreted endo-1,4-bglucanases are non-crystalline cellulose and xyloglucans.…”
Section: Sucrose Affects Expression Of Atcel2 But Not Kor3supporting
confidence: 77%
See 3 more Smart Citations
“…Upregulation of AtCel2 triggered by high sucrose concentration in the medium indicates its involvement in cellulose biosynthesis as previously suggested by Ohmiya et al (2000) and Shani et al (2006) for other endo-1,4-b-glucanases. Putative cell wall substrates of secreted endo-1,4-bglucanases are non-crystalline cellulose and xyloglucans.…”
Section: Sucrose Affects Expression Of Atcel2 But Not Kor3supporting
confidence: 77%
“…Other studies revealed that expression of endo-1,4-bglucanases depends on addition of sucrose as shown for PopCel1 and PopCel2 (Ohmiya et al, 2000) and for AtCel1 . Based on these results the authors suggest that the EGases are involved in cellulose biosynthesis.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Other cellulases in GH9, lacking the membrane-spanning domain, had ESTs that were broadly distributed among poplar tissues (Table III). These cellulases may act on amorphous cellulose in the cell wall and, by doing so, increase cell wall plasticity (Ohmiya et al, 2000(Ohmiya et al, , 2003Park et al, 2003).…”
Section: Cellulosementioning
confidence: 99%